Concentration and bioavailability of fluoride in mouthrinses prepared in dispensing pharmacies - Tabchoury,Cínthia Pereira Machado (2005)
Considering the importance of medication quality control and that mouthrinses for dental caries prevention have commonly been prepared in dispensing pharmacies, this study assessed formulations containing 0.05% NaF acquired from 6 dispensing pharmacies in the city of Piracicaba, S.P. The mouthrinse formulations were purchased in 3 separate periods and coded from A to F. Fluoride ion (F-) concentration was determined in all formulations in the 3 periods, and in those acquired in the 3rd period, the bioavailability of fluoride with dental enamel with caries-like lesions and the pH of products were evaluated. A solution of 0.05% NaF and distilled deionized water were used, respectively, as positive and negative controls. In the bioavailability analysis, fluoride present in dental enamel was determined removing, by acid etching, two layers of enamel; fluoride in the acid extract was determined with a specific electrode. The mouthrinses prepared in 5 pharmacies presented a F- concentration close to the expected value, except for the product prepared in one of them, in which a mean of 0.01% NaF was found. All products were more efficient than the negative control (p<0.05) in terms of reactivity with dental enamel, but differences among them were observed with regard to the positive control (p<0.05). The data suggest that a quality control program should be implemented in dispensing pharmacies to guarantee the quality of fluoridated mouthrinses formulated.